Adolescent Emotional Intelligence Based on Perceptions of Parenting Styles - Eli Sandra; Puspa Rahayu Utami Rahman; Yulyanti Minarsih (Journal of Psychological Perspective, 2026)
Middle adolescents are highly vulnerable to emotional regulation difficulties, necessitating supportive parental guidance. This study aims to examine the contribution of adolescents' perceptions of paternal and maternal parenting styles to their emotional intelligence, evaluated both as individual predictors (partially) and through two-predictor combined models. It was hypothesized that both paternal and maternal parenting styles significantly contribute to middle adolescents' emotional intelligence, both partially and within combined linear models. A quantitative approach was employed, involving 410 adolescents aged 15–18 years in Karawang Regency, selected via convenience sampling. Data were gathered using the Assessing Emotions Scale (AES) and the Parental Authority Questionnaire (PAQ). Data analysis was performed using linear regression analysis. The results indicated that when analyzed as individual predictors, only maternal authoritative parenting style contributed significantly, whereas all dimensions of paternal parenting styles showed no significant independent effect. However, the two-predictor combined models demonstrated that pairs of paternal and maternal parenting dimensions jointly contributed significantly, particularly when the maternal figure implemented an authoritative parenting style, which acted as the primary anchor of the model. The largest combined variance was contributed by the combination of maternal authoritative and paternal authoritarian styles (R2 = .141). This study underscores the critical role of maternal authoritativeness in buffering adolescent emotional outcomes within industrial contexts, while highlighting the need for enhanced paternal quality of involvement.